A 55‐year‐old natural experiment gives evidence of the effects of changes in fire frequency on ecosystem properties in a seasonal subtropical dry forest. (22nd November 2018) - Kowaljow, Esteban; Morales, Mariano S.; Whitworth‐Hulse, Juan I.; Zeballos, Sebastián R.; Giorgis, Melisa A.; Rodríguez Catón, Milagros; Gurvich, Diego E.
Abstract: Fire frequency has been highlighted as an important component of fire effects on ecosystems; nevertheless, there is scarce information about how fire modulates changes in ecosystem properties, particularly for subtropical dry forests. A long‐term natural experiment and a multiscale approach were used to analyze changes in ecosystem properties in a subtropical dry forest subjected to contrasting fire regimes. Measurements were taken in two adjacent sites that had contrasting fire regimes (low/high fire frequency), and vegetation and soil analyses were combined with dendrochronological methods. Ten plots (20 × 20 m) were established in each site and soil (depth, chemical, and biological properties), and vegetation (species composition and growth of the dominant tree, Lithraea molleoides ) variables were measured. Fire scars in L. molleoides were useful in determining fire history. Shrubs and grasses were more abundant in the high fire frequency site, with a high cover of the exotic grass Melinis repens, whereas trees and vines were more abundant in the low fire frequency site. Soil of the high fire frequency site tended to have lower C and nutrient content as well a significant lower depth than those of the low fire frequency site. Growth of L. molleoides individuals was lower in the high fire frequency site. Our results suggest that the long‐term effects of high fire frequency probably increase both soil loss and fire frequency in the future due to changes in plant composition, indicating that frequent burning is not a sustainable management option for this seasonal subtropical dry forest.